Addressing Fundamental Challenges of Si/Gr Electrodes with High Silicon Contents Using Innovative Bilayer Electrode Structure Design - Jeong Hyeon Yoo; Sung Joon Park; Cheol Bak; Yong Min Lee; Ki Jae Kim (Small Structures)
The extremely high volume change of Si during alloying and dealloying in the charge/discharge process is a key challenge for increasing the Si content in Si/Gr electrodes. To address these fundamental challenges, a sophisticated bilayer Si/Gr electrode composed of an upper layer with a porous structure and a lower layer with a compact structure to increase the Si content while enhancing the long‐term cycling stability of the electrode is designed. The unique structure of the bilayer Si/Gr electrode is achieved by controlling the densities of the upper and lower electrode layers. The porous structure of the upper layer can accommodate the volume expansion of Si, thereby increasing the Si content of the Si/Gr electrode. The compact structure of the lower layer can suppress the delamination of the electrode by the volume expansion of Si due to its high binding strength with the current collector, thus ensuring the long‐term stability of the Si/Gr electrode. Consequently, because of the distinct features of the upper and lower layers in the bilayer Si/Gr electrode, superior cyclability is achieved despite an increase in the total Si content to 30 wt% in the Si/Gr electrode, with a specific capacity of 534.8 mAh g−1 after 100 cycles.